The merger of three state owned shariah bank in Padangsidimpuan - Kurniawan, Ferdy; Hasibuan, Abdul Nasser; Nasution, Ananda Anugrah (ASNAF : Journal of Economic Welfare, Philantrophy, Zakat and Waqf, 2023)
Abstract Purpose - The objective of this study is to identify the positive and negative impacts of the merger of Islamic banks on the community or customers and employees of Islamic banks in Kota Padangsidimpuan. Method - To address this issue, this study employed a qualitative descriptive method. Data collection for this study used the interview technique. This study involved 15 informants from the local community and 5 informants of bank employees. Results - The merger of Islamic banks in Kota Padangsidimpuan brought both advantages and challenges for the community and bank employees. On the bright side, the merger expanded the reach of Islamic banking services, which projected there are more people could now access essential financial products and services like savings accounts, loans, and investments. This potentially boosted financial inclusion and economic activity in the city. The merger also enhanced job security for employees, by becoming part of a larger, state-owned enterprise like Bank Syariah Indonesia (BSI), the employees gained stability and potential career advancement opportunities. However, there were also some shortcomings, the merger led to the limited access to physical banking infrastructure: The lack of new ATMs and branch offices following the merger might have inconvenienced some customers, especially those in remote areas. In addition, it adjusted the period for employees, which adapting to new systems and regulations after the merger could have been challenging for some employees, requiring additional training and support. Overall, the merger's impact was mixed. While it provided broader access to Islamic banking and job security for employees, it also highlighted the need for further expansion of physical banking infrastructure and support for employees during transitions. Addressing these challenges could help maximize the positive outcomes of the merger for the community and bank employees in Kota Padangsidimpuan. Limitation – The generalizability of the findings may be limited due to the study's focus on a single merged Islamic bank in one city. Practical Implicative - The consolidation of three Islamic banks marks a significant step in enhancing Sharia-compliant financial services. This merger has the potential to benefit both the community and the national economy. By uniting resources and expertise, the new entity offer a wider range of Sharia-approved products and services, catering to the specific needs of the community while also contributing to broader societal well-being and economic development.